PEMBERIAN PUPUK DAUN TERHADAP PERTUMBUHAN BIBIT Gyrinops caudata (Gilg) Domke ( Granting Of Leaf Growth Fertilizer Seed Gyrinops caudata (Gilg) Domke ) - Sumanto Basahona; Marthen T. Lasut; J. A. Rombang; Alfonsius Thomas (COCOS, 2013)
ABSTRACTGyrinops caudata is one of gaharu plant family Thymeleaceae no less quality than the other speciesin Indonesia. Foliar fertilizers are inorganic fertilizers Gandasil D macro and micro, and a specialpowder for vegetative growth of plants. The purpose of this study was to determine the effect offoliar fertilizers on the growth of seedlings Gandasil D Gyrinops caudata by using completelyrandomized design (CRD) with 4 treatments and 5 replications. Treatment A concentration of 0 g / lof water, the treatment of B concentration of 2 g / l of water, (0.012 g dose), treatment Cconcentration of 4 g / l of water, (0.024 g dose) and treatment D concentration of 6 g / l of water,(dose 0.036 g). The variables measured were plant height increment, diameter increment in thenumber of stems and leaves. The results showed that the application of fertilizer to the seed leavesGandasil D Gyrinops caudata give significantly different results at high accretion, increased stemdiameter and in the number of leaves. Treatment D with a concentration of 6 g / l of water, (0.036 gdose) showed good results in plant growth compared with the other treatments.Key words : Gyrinops caudata, Agarwood, leaf manure Gandasil D